An Assessment for "Quality of Life! through "Urban Poverty" Perspective - Elif Kýsar Koramaz (European Regional Science Association (ERSA), 2013)
Quality of Life, as the holistic experience of life, occurs through the interaction of resources and conditions of life and society?s needs, expectations and evaluations concerning those resources and conditions. Land use attributes and their spatial organization, public services and utilization of these services are regarded as the main indicators of Quality of Life (QoL) in an urban environment. As assessments for these indicators bring out the geography of QoL in a city, they also reveal the forms of deprivations faced in the city. In other words, QoL research in urban areas can depict the deprivation forms those the vulnerable social groups suffer in poor neighbourhoods. With a conceptualization of urban poverty as the state cumulative deprivations which occurs through the interaction of different domains and dimensions of life, this paper aims to discuss, if an urban QoL research can act as a tool to fight against urban inequality and poverty. With this aim, indicators of QoL are analyzed and compared among different neighbourhoods and socio-economic groups in residential areas of Ýstanbul. The findings of the paper indicate the spatial differentiation of QoL as well as the forms and levels of deprivations which the vulnerable social groups face in Istanbul. Through the assessment of QoL, the results indicate that level QoL differ in Istanbul following the pattern of residential area characteristics such as development type, urban fabric and spatial integration to the infrastructure and public services. In this context, residential areas located on the outskirts and previously started to develop as squatter settlements are subject to urban poverty in terms of multiple deprivations and spatial and social disintegration. The study results lead to spatially addressed policies and strategies which would enhance QoL and defeat urban poverty in deprived neighbourhoods in Istanbul. Finally the paper questions if an understanding of QoL through the perspective of urban poverty offers the possibilities of social equity and integration of the vulnerable social groups to the urban social fabric.
Keywords: R23; 330; Population; Neighborhood Characteristics